ERK signaling controls productive HIF‐1 binding to chromatin and cancer cell adaptation to hypoxia through HIF‐1α interaction with NPM1 - Kreon Koukoulas (Wiley, 2021)
The hypoxia‐inducible factor HIF‐1 is essential for oxygen homeostasis. Despite its well‐understood oxygen‐dependent expression, regulation of its transcriptional activity remains unclear. We show that phosphorylation by extracellular signal‐regulated kinases1/2 (ERK1/2), in addition to promoting HIF‐1α nuclear accumulation, also enhances its interaction with chromatin and stimulates direct binding to nucleophosmin (NPM1), a histone chaperone and chromatin remodeler. NPM1 is required for phosphorylation‐dependent recruitment of HIF‐1 to hypoxia response elements, its interaction with acetylated histones, and high expression of HIF‐1 target genes under hypoxia. Transcriptome analysis revealed a significant number of hypoxia‐related genes commonly regulated by NPM1 and HIF‐1. These NPM1/HIF‐1α co‐upregulated genes are enriched in three different cancer types, and their expression correlates with hypoxic tumor status and worse patient prognosis. In concert, silencing of NPM1 expression or disruption of its association with HIF‐1α inhibits metabolic adaptation of cancer cells and triggers apoptotic death upon hypoxia. We suggest that ERK‐mediated phosphorylation of HIF‐1α regulates its physical interaction with NPM1, which is essential for the productive association of HIF‐1 with hypoxia target genes and their optimal transcriptional activation, required for survival under low oxygen or tumor growth.